The metabolic deterioration that antedates diabetes: personal trajectories of HbA1c and fasting glucose as early indicators and possible triggers for intervention. Issue 1 (8th January 2013) - Dankner, Rachel; Bergman, Michael; Danoff, Ann; Qureshi, Sana; Whitford, Ian; Kaviani, Nargess; Dynkevich, Yevgeniya; Roth, Jesse
Summary HbA1c testing has become an accepted means of diagnosing diabetes as an alternative to blood glucose levels. However, population‐based norms of glucose and of HbA1c levels do not enable the detection of diabetes at an early enough stage to thwart complications. Personal trajectories of glucose levels show steep increases a number of years prior to diabetes diagnosis. Here, we hypothesize that a comparable time‐dependent deviation in an individual's HbA1c level may be an early manifestation of disease that should prompt lifestyle modifications. We predict that analysis of personal trajectories of glucose and of HbA1c will promote earlier intervention and a greater reduction in disease complications than current standards, which are based on population‐based norms. Copyright © 2012 John Wiley & Sons, Ltd.